问题 解答题
5
12
+
4
9
+
7
12
+
5
9

5
6
-(
1
5
+
1
6
)

1
7
8
-
4
5
-
1
5

2
7
+
3
14
+
4
21

7
8
-(
1
3
-
1
12
)

3
4
-
2
3
+
1
6
答案

(1)

5
12
+
4
9
+
7
12
+
5
9

=(

5
12
+
7
12
)+(
4
9
+
5
9
),

=1+1,

=2;

(2)

5
6
-(
1
5
+
1
6
),

=

5
6
-
1
6
-
1
5

=

2
3
-
1
5

=

7
15

(3)1

7
8
-
4
5
-
1
5

=1

7
8
-(
4
5
+
1
5
),

=1

7
8
-1,

=

7
8

(4)

2
7
+
3
14
+
4
21

=

1
2
+
4
21

=

29
42

(5)

7
8
-(
1
3
-
1
12
),

=

7
8
-
1
12

=

19
24

(6)

3
4
-
2
3
+
1
6

=

1
12
+
2
12

=

1
4

选择题
单项选择题